Risk of prolonged opioid use among cancer patients undergoing curative intent radiation therapy for head and neck malignancies. (May 2019) - Smith, William H.; Luskin, Ian; Resende Salgado, Lucas; Scarborough, Bethann M.; Lin, Jung-Yi; Özbek, Umut; Miles, Brett A.; Gupta, Vishal; Bakst, Richard L.
Highlights: Many patients require long-term opioids following head and neck radiation therapy. The risk of prolonged opioid use depends on patient- and treatment-specific factors. Induction chemotherapy and alcohol abuse predict for prolonged opioid use. Early targeted intervention may mitigate the risk of prolonged opioid use. Abstract: Objective: Patients undergoing radiation treatment (RT) for head and neck malignancies often suffer significant disease- and treatment-related pain requiring opioids for effective management. However, the prevalence and associated risk factors of prolonged opioid use in this population remain poorly characterized. We sought to quantify the rate of prolonged opioid use among opioid naïve patients receiving curative-intent RT for head and neck malignancies and to identify associated risk factors. Methods: We retrospectively identified patients who had undergone RT for head and neck malignancies at our institution between Jan 2011 and Sept 2017. Our primary endpoint was persistent opioid use 6-months following completion of RT. Patients were included if they were opioid-naïve, underwent curative intent RT, had adequate follow-up, and did not have residual or recurrent disease within our follow-up period. Univariable and multivariable logistic regression was utilized to identify risk factors for prolonged opioid use. Results: We identified 311 patients meeting our inclusion criteria; 40 (12.9%) continued to use opioids 6-months following RT. Univariable analysis found current smoking, alcohol abuse, RT dose, treatment to the bilateral necks, induction chemotherapy, concurrent chemotherapy, PEG tube, daily milligram morphine equivalents, and adjuvant analgesic medication use to be positively associated with prolonged opioid use; prior surgery was negatively associated with prolonged opioid use. Delivery of induction chemotherapy (OR 2.86, CI (95%) 1.32–6.21) and alcohol abuse (OR 3.75, CI (95%) 1.66–8.47) remained statistically significant on multivariable analysis. Conclusion: The prevalence of prolonged opioid use in previously opioid naïve patients undergoing curative intent head and neck RT was just under 13%. Patients with history of alcohol abuse and those who undergo induction chemotherapy were most at risk.